Bioaccumulation of Trace Metals in Biofilms Formed on Aluminium and Steel in Aquatic Environment - P, Muhamed Ashraf; Thomas, Saly N (Fishery Technology, 2025)
Knowledge on initial bioadhesion and composition of micro and macro nutrients within the biofilm matrix are recognised as essential for understanding the formation of biofilms. This communication highlights the heavy metal accumulation pattern in biofilms, influenced by the substrate and seasons. Natural biofilms were simultaneously grown on aluminium and steel panels for 72 hours by exposing them in the aquatic environment. Accumulation of toxic and nutrient metals in biofilms on different substrates and its seasonal variation were studied. Biofilms grown within 24 hours had shown significantly (p < 0.05) higher concentrations of trace metals in both the metal substrates. Trace metals accumulated over the substrates varied in different seasons. Among the metals, the accumulation of zinc was more during all the seasons. Biofilms grown on steel, concentrated more metals than on aluminium